1995
DOI: 10.1177/000992289503400505
|View full text |Cite
|
Sign up to set email alerts
|

The Ohio Bicycle Injury Study

Abstract: To understand bicycle injuries and determine how to prevent them, we designed prospectively a descriptive study of bicycle-crash-related admissions in July 1993 to 10 major Ohio hospitals that admit child trauma patients. All patients studied were under the age of 16. In the 52 cases (38 male, 73%), impact with another vehicle accounted for 23 (44%) crashes. Of these crashes, only three (13%) were caused by definite motor vehicle operator error, and all 20 (87%) of the remaining motor vehicle-bicycle collision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 3 publications
0
14
0
2
Order By: Relevance
“…2-8,10 -14,17,29,30,51,52 Head and traumatic brain injuries are a common sequela of bicycle accidents. 5,7,[11][12][13][14] Bicycle helmets help prevent the occurrence and severity of head, traumatic brain, and facial injuries. 20 -26,33 Despite this information, most people continue to bicycle without helmets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2-8,10 -14,17,29,30,51,52 Head and traumatic brain injuries are a common sequela of bicycle accidents. 5,7,[11][12][13][14] Bicycle helmets help prevent the occurrence and severity of head, traumatic brain, and facial injuries. 20 -26,33 Despite this information, most people continue to bicycle without helmets.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have suggested that people do not purchase bicycle helmets because of expense or low income. 13 cational campaigns. 18,34 -36,47,55,56 In our survey, 4.6% of children, 4.8% of adolescents, and 4.3% of adults selected expense as a reason not to wear a bicycle helmet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar barriers to helmet use have been reported elsewhere. [28][29][30][31][32][33][34][35] Approaches to increasing helmet use Approaches to improving helmet use include consumer incentives, education surrounding helmet safety, and legislation. Consumer incentives can include helmet rentals, coupons, mailings at point of sale, discounts and promotion, and loaner helmets.…”
Section: Barriers To Bicycle Helmet Usementioning
confidence: 99%